Determinanty synchronizacji cykli koniunkturalnych w Unii Europejskiej: lata 1991-2011 (Myśl Ekonomiczna i Polityczna, 2013)
Further economic and monetary integration in Europe is currently onhold due to the economic crisis and even questions about a possible Greeceexile. Especially in those conditions it is important to see whether integratedEurope can handle future problems and if economic and monetary integrationcan be helpful or rather more problematic. The main aim of this paper is tocheck to what degree business cycles are synchronized in the Eurozone andthe European Union and what the main determinants of business cyclessynchronization are. To achieve it, the following steps are taken. Firstly, weturn to optimum currency area theory to see what conditions need to bemet if the European Union and the Euro Area can use common monetarypolicy to deal with some economic shocks. Then all necessary methodologicalexplanations are put. Later on, the preliminary data analysis is employedto see how business cycles and their determinants have been acting duringthe last 20 years. Finally, panel data analysis is used to check how thosedeterminants actually influence business cycles synchronization. The mainfinding of the article is that even though business cycles synchronizationhas been progressing in the European Union and the Euro Area, so has thespecialization – divergence in production structure. This may result in lesssynchronized business cycles in the future.